Lateral Heterostructures: 1D p–n Junction Electronic and Optoelectronic Devices from Transition Metal Dichalcogenide Lateral Heterostructures Grown by One‐Pot Chemical Vapor Deposition Synthesis (Adv. Funct. Mater. 27/2021). (2nd July 2021) - Najafidehaghani, Emad; Gan, Ziyang; George, Antony; Lehnert, Tibor; Ngo, Gia Quyet; Neumann, Christof; Bucher, Tobias; Staude, Isabelle; Kaiser, David; Vogl, Tobias; Hübner, Uwe; Kaiser, Ute; et al.
Abstract : In article number 2101086, Antony George, Andrey Turchanin, and co‐workers present the synthesis of monolayer MoSe2 ‐WSe2 lateral heterostructures with the atomically sharp 1D boundaries via a one‐pot chemical vapor deposition process. Various p–n junction devices including rectifiers, solar cells, photodetectors, ambipolar transistors, and light emitting diodes are demonstrated using these atomically thin heterostructures.